THE CRIME OF TREASON COMMITTED JOINTLY FROM THE PERSPECTIVE - Wijanarko, Gapung; Pratiwi, Siswantari; Sinaga, Parbuntian (JILPR Journal Indonesia Law and Policy Review, 2024)
In general, treason is an action carried out by a person or group of citizens by questioning the legal order that applies in a country. They took this action because of dissatisfaction with the administration of government, so that citizens carried out various actions that were against the law. Or it can be said to be a discrepancy between an individual or group of people and government regulations. The problems in this journal are how to prove unlawful acts committed jointly by the perpetrators of the crime of treason (Aanslag) in crimes that threaten state security and how each perpetrator of treason is held accountable in the judge's decision in Decision Number 23/PID/2020 /PT.AMB and Decision Number 24/PID/2020/PT. AMB. The research method is carried out using the normative legal method because it describes the applicable laws and regulations and is linked to legal theories in the practice of implementation related to problems that will be researched using this method as well, it will describe/describe the facts that actually occur as reflection of the implementation of statutory regulations and legal principles linked to legal theories and implementation practices. Based on this research, it can be understood that the benchmark for determining whether an act is considered treason is an act that is indicated to endanger the head of state or head of government so that the head of state or head of government is unable to carry out his duties properly. The criminal liability of the perpetrators of the crime of treason is joint responsibility based on Article 106 of the Criminal Code in conjunction with Article 55 paragraph (1) 1 of the Criminal Code, namely those who committed, ordered to commit, and participated in committing the criminal act.